Integrating the linguocultural component and mind-map method to develop a trilingual e-dictionary of biological terms - Kalizhanova, A.; Maryshkina, T.; Ishmuratova, M.; Ibrayeva, B. (Periodico Tche Quimic, 2020)
The national project Trinity of Languages announced in Kazakhstan has brought forward multilingual education throughout the country. The project requires the implementation of rigorous learning tools to master the Kazakh, Russian and English languages within trilingualism. An e-dictionary to be used in content and language integrated learning is among modern e-tools promoted in a trilingual school environment. A user-friendly biological e-dictionary will help high school learners grasp fundamental concepts in natural sciences. The article aims to describe how to analyze and systemize the lexicographic material selected for developing a trilingual e-dictionary of biological terms for Kazakhstani school learners. Determining sources of vocabulary chosen was based upon a linguocultural approach, which highlights the cultural aspect embodied in the language, and mind-mapping, which allows deconstructing complex topics graphically. Twenty-eight items were selected to cover the biology school course, which was later analyzed and systemized to consistently present generic and species features via mind-mapping. Then organic unification of the items and compositional parameters of the e-dictionary were determined. The obtained findings show that a linguocultural component is embedded in a trilingual e-dictionary of biological terms that are taken from relevant Kazakh and Russian school textbooks (grades 6-11). The selected items are classified and subject to linguocultural analysis in conceptual groups which may show phytonyms and zoonima. The items are supplied with an adequate linguocultural commentary taken from English-language reference books and websites. The conceptual groups and linguistic analysis are displayed via the mind map Coggle used for the e-dictionary frame formation. The proposed linguocultural component embedded in the edictionary is rare in other existing trilingual e-dictionaries since they focus primarily on lexicographic material and their visual representation. Overall, the trilingual e-dictionary created in mind-mapping software is an effective etool for high school learners to study biological terms with their linguocultural commentaries. © 2020 Tche Quimica Group. All rights reserved.
Integrando o componente linguo-cultural e o método do mapa da mente para desenvolver um e-dicionário trilíngue de termos biológicos
Keywords: trilingualism; e-dictionary; lexicographic units; linguocultural component; mind map